School Health: an essential strategy in promoting community resilience and preparedness for natural disasters - Kenzo Takahashi; Mitsuya Kodama; Ernesto R. Gregorio; Sachi Tomokawa; Takashi Asakura; Jitra Waikagul; Jun Kobayashi (Taylor & Francis Group, 2015)
Background: The Third UN World Conference on Disaster Risk Reduction recommended the implementation of the Sendai Framework for Disaster Risk Reduction 2015-2030, which aims to achieve substantial risk reduction and to avoid various disaster-associated losses, including human lives and livelihoods, based on the lessons from the implementation of the Hyogo framework. However, the recommendations did not lay enough stress on the school and the Safe School Concept, which are the core components of a disaster response. Objective: To raise the issue of the importance of schools in disaster response. Results: For human capacity building to avoid the damage caused by natural disasters, we should focus on the function of schools in the community and on school health framework. Schools perform a range of functions, which include being a landmark place for evacuation, acting as a participatory education hub among communities (students are usually from the surrounding communities), and being a sustainable source of current disaster-related information. In 2007, the Bangkok Action Agenda (BAA) on school education and disaster risk reduction (DRR) recommended the integration of DRR into education policy development, the enhancement of participatory mechanisms to improve DRR education, and the extension of DRR education from schools to communities. Based on our discussion and the recommendations of the BAA, we suggest that our existing challenges are to construct a repository of disaster-related lessons, develop training materials based on current information drawn from previous disasters, and disseminate the training to schools and communities. Conclusions: Schools linked with school health can provide good opportunities for DRR with a focus on development of school health policy and a community-oriented participatory approach.